2013
DOI: 10.2500/aap.2013.34.3641
|View full text |Cite
|
Sign up to set email alerts
|

Small airway dysfunction by impulse oscillometry in asthmatic patients with normal forced expiratory volume in the 1st second values

Abstract: Small airways are relevant to the pathophysiology of asthma. We investigated whether in asthmatic patients with normal forced expiratory volume in the 1st second (FEV(1)) values, impulse oscillometry system (IOS), as a measure of small airway function, contributed additional information to spirometry either at baseline or after bronchodilator, and whether it was related to the disease control. The fall in resistance from 5 to 20 Hz (R5-R20) and reactance at 5 Hz (X5) by IOS and spirometry measures of small ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 0 publications
7
39
0
1
Order By: Relevance
“…An advantage of IOS may be the detection of subtle changes in a patient’s airway function earlier than with conventional spirometry [35, 43] and some data suggest that IOS can be used to assess abnormal distal airway function, even in the setting of normal spirometry [35, 44]. Especially, airway reactance was also correlated with ground-glass opacity [45].…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of IOS may be the detection of subtle changes in a patient’s airway function earlier than with conventional spirometry [35, 43] and some data suggest that IOS can be used to assess abnormal distal airway function, even in the setting of normal spirometry [35, 44]. Especially, airway reactance was also correlated with ground-glass opacity [45].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, on the basis of all this evidence, we may speculate that in the present study, abnormal FEF 25-75% in symptomatic subjects with normal FEV 1 can be considered a marker of early airway obstruction without involvement of the proximal/central airways. Pisi et al [41] suggested investigating small airway dysfunction in asthmatic patients with normal FEV 1 values by using an impulse oscillometry system as an alternative to spirometry.…”
Section: Discussionmentioning
confidence: 99%
“…Small airway function as evaluated by peripheral airway IOS indices, correlated better with clinical symptoms and asthma control than spirometry; furthermore, greater small-airways reactance was associated with loss of asthma control. Pisi et al investigated the presence of SAD based on increased peripheral airway IOS indices in 33 adult asthmatic patients with normal FEV1 values [56]. Small airway dysfunction, as assessed by IOS and spirometry, was associated with poor disease control, assessed by the Asthma Control Test.…”
Section: Introductionmentioning
confidence: 99%